An An Implementation of Micro, Small, and Medium Enterprise (MSME) Opportunities and Challenges In The Pandemic Era : A Literature Review - Deddy Sulestiyono; Maya Aresteria; Lia Iva Budi Lestiani (Universitas Ngudi Waluyo, 2021)
Abstract ____________________________________________________________ This study aims to describe the opportunities that can be achieved by prospective MSME actors in the pandemi era. In this study, the qualitative methods and descriptions of students who have succeeded in becoming MSME actors in this pandemi era are explained so that they can directly apply the knowledge gained to in their lives as the implementation of Kampus Merdeka : Merdeka Belajar, it can further be applied by all prospective MSME players, so it can help to improve the economy in Indonesia.